2021
DOI: 10.1021/acs.oprd.1c00101
|View full text |Cite
|
Sign up to set email alerts
|

Proof-of-Concept Design of an In-Line pH Neutralization System with Coarse and Fine Adjustments for the Continuous Manufacturing of Pharmaceuticals

Abstract: In the continuous manufacturing of pharmaceuticals, in-line monitoring and control are essential. Many pharmaceutical manufacturing processes require pH adjustment. Here, an in-line pH neutralization system with both coarse and fine adjustments was designed, and promising results were obtained. In nonbuffered conditions, the proposed two-pump system was able to control the fluctuations within approximately 2 pH units near the equivalence point, for both aqueous solutions and organic− H 2 O mixtures with strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, a large difference between the p K a of HCl (−6.3) and set point pH of 7 makes it challenging to control pH in continuous experiments where a slight deviation/fluctuation in the pump flow rate is detrimental. For better pH control, the difference between the desired pH (7 in the present case) and the p K a of the acidifying agent should be minimal . The examination of p K a values of different acids viz.…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, a large difference between the p K a of HCl (−6.3) and set point pH of 7 makes it challenging to control pH in continuous experiments where a slight deviation/fluctuation in the pump flow rate is detrimental. For better pH control, the difference between the desired pH (7 in the present case) and the p K a of the acidifying agent should be minimal . The examination of p K a values of different acids viz.…”
Section: Resultsmentioning
confidence: 95%
“…Finally, different types of pumps can be employed to fine tune a given application. [162] When making tablets for ultra-lowdose drugs using twin-screw wet granulation, Démuth et al showed that syringe pumps generated lower deviation of drug content in tablets compared to peristaltic or piston-driven pumps. This is important as ultra-low-dose drugs require higher degrees of precision versus normal dosages.…”
Section: Pumpingmentioning
confidence: 99%
“…By integrating pumps with in‐line monitoring and control, they were able to control the pH fluctuation within 2 pH units near the equivalence point. Finally, different types of pumps can be employed to fine tune a given application [162] . When making tablets for ultra‐low‐dose drugs using twin‐screw wet granulation, Démuth et al .…”
Section: Unit Operationsmentioning
confidence: 99%
“…In-line pH sensors, designed for continuous data measurement, have been used in the biotech and pharmaceutical industries for a number of years [48][49][50]. However, there are a limited number of electrode systems capable of providing in-situ pH measurements at temperatures greater than 100 • C and at pressures greater than saturated water pressure.…”
Section: Industrial Applications Of In-line Ph Measurement Under Chal...mentioning
confidence: 99%